2007
DOI: 10.1016/j.gene.2006.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pre-insertion loci of de novo L1 insertions

Abstract: The human Long Interspersed Element-1 (LINE-1) and the Short Interspersed Element (SINE) Alu comprise 28% of the human genome. They share the same L1-encoded endonuclease for insertion, which recognizes an A+T-rich sequence. Under a simple model of insertion distribution, this nucleotide preference would lead to the prediction that the populations of both elements would be biased towards A+T-rich regions. Genomic L1 elements do show an A+T-rich bias. In contrast, Alu is biased towards G+C-rich regions when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 59 publications
5
31
0
Order By: Relevance
“…S1E, S4;Singer et al 1983;Scott et al 1987;Luan et al 1993;Moran et al 1996;Jurka 1997). The average GC content of de novo L1 insertion sites within a 50-bp and 20-kb window of the endonuclease cleavage position was 30% and 38%, respectively, consistent with a previously described preference of L1 for AT-rich regions (Supplemental Table 4; Szak et al 2002;Boissinot et al 2004;Gasior et al 2007). One insertion (insertion #5) (Fig.…”
Section: Resultssupporting
confidence: 86%
“…S1E, S4;Singer et al 1983;Scott et al 1987;Luan et al 1993;Moran et al 1996;Jurka 1997). The average GC content of de novo L1 insertion sites within a 50-bp and 20-kb window of the endonuclease cleavage position was 30% and 38%, respectively, consistent with a previously described preference of L1 for AT-rich regions (Supplemental Table 4; Szak et al 2002;Boissinot et al 2004;Gasior et al 2007). One insertion (insertion #5) (Fig.…”
Section: Resultssupporting
confidence: 86%
“…As a result of unequal selective pressures across the genome, the patterns of element distribution observed via genome sequencing will not necessarily coincide with the initial pattern of insertions. For example, although L1 elements in humans are generally found in gene-poor AT-rich regions, data from cell culture suggest that this may be an effect of post-insertional processes rather than an initial insertion preference dictated by L1 biology (Ovchinnikov et al 2001;Graham and Boissinot 2006;Gasior et al 2007). Similar results were obtained when L1 integration events were characterized in transgenic animals Babushok et al 2006), suggesting that the discrepancy in the distribution between new and old L1 integration events is likely to arise from post-insertional selection pressures.…”
Section: Genome Research 347mentioning
confidence: 99%
“…L1 elements are present at a higher density on the X chromosome than any other chromosome (Lander et al 2001), and it remains possible that some of this density increase may represent insertion preference. However, there was no detectable enrichment of L1 element insertions on the X chromosome in tissue culture studies that directly measures de novo L1 insertions (Graham and Boissinot 2006;Gasior et al 2007), and the enrichment on the X chromosome has largely been ascribed to lower recombination rates and corresponding reduction in the efficiency of negative selection among the sex chromosomes (Boissinot et al 2001). In contrast, 31 endogenous retroviral insertions in mice (Ostertag and Kazazian 2001a;Maksakova et al 2006) have been detected, and none of those insertions was found to reside on the X chromosome.…”
Section: Insertional Mutagenesis and Diseasementioning
confidence: 99%
“…3A). L1s are also enriched in A/T-rich genomic regions (Gasior et al 2007). Variation in L1 polymorphism densities along chromosomes is not due simply to differences in WGS trace coverage (Supplemental Fig.…”
Section: L1 Polymorphismsmentioning
confidence: 99%